2015
DOI: 10.3892/ijmm.2015.2148
|View full text |Cite
|
Sign up to set email alerts
|

Soluble uric acid increases NALP3 inflammasome and interleukin-1β expression in human primary renal proximal tubule epithelial cells through the Toll-like receptor 4-mediated pathway

Abstract: Urate crystals activate innate immunity through Toll like receptor 4 (TLR4) activation, leading to the formation of the NACHT, LRR and PYD domains-containing protein 3 [NALP3; also known as NOD-like receptor family, pyrin domain containing 3 (NALP3) and cryopyrin] inflammasome, caspase-1 activation and interleukin (IL)-1β expression in gout. However, whether elevated serum uric acid (UA) levels are associated with the development and progression of renal diseases without renal urate crystal deposition remains … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
105
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(122 citation statements)
references
References 51 publications
5
105
0
1
Order By: Relevance
“…XO inhibition had no significant effect on the level of urine sodium (Supplemental Table 2). Uric acid increases kidney fibrosis and inflammation, in part, through upregulation of fibronectin and TLR4 expression [17]. Therefore, we examined expression of fibronectin and TLR4 in kidney tissue.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…XO inhibition had no significant effect on the level of urine sodium (Supplemental Table 2). Uric acid increases kidney fibrosis and inflammation, in part, through upregulation of fibronectin and TLR4 expression [17]. Therefore, we examined expression of fibronectin and TLR4 in kidney tissue.…”
Section: Resultsmentioning
confidence: 99%
“…We also observed that consumption of a WD was associated with increased renal tissue TLR4, and that this process was mitigated by allopurinol administration. Importantly, TLR4 is implicated in the kidney inflammatory responses and uric acid increases the expression of TLR4 in kidney [17]. Signaling through toll-like receptors activates dendritic cells and inflammatory cytokines to promote inflammation and fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…2007; Xiao et al. 2015) and therefore, can be important targets of several TLR4 ligands in the kidney. LPS is a well-established and studied TLR4 ligand, and is found in increased levels among CKD patients (McIntyre et al.…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, it has been shown that when UA increases in a cell, there is an activation of NADPH oxidase in the kidney which increases oxidative stress and various pro-inflammatory and vasoactive mediators that lead to renal vasoconstriction, glomerular hypertension and eventually tubulointerstitial fibrosis and glomerular sclerosis [23]. In addition, both soluble and crystalized UA can also induce inflammasome activation and apoptosis in proximal tubule cells [24,25]. Therefore, it is possible that the primary protective effect of reducing UA levels is to preclude the activation of such prooxidant and proinflammatory pathways.…”
Section: Discussionmentioning
confidence: 99%